2018
DOI: 10.1007/s12040-018-1017-1
|View full text |Cite
|
Sign up to set email alerts
|

The age of the Nodular Limestone Formation (Late Cretaceous), Narmada Basin, central India

Abstract: The age of the marine Nodular Limestone Formation of the Bagh Group is refined at Substage level through ammonoid and inoceramid index taxa. The study is based on the fresh collections from three welldefined successive intervals (Lower Karondia, Upper Karondia and Chirakhan members) of this formation having excellent exposures in different localities of the Narmada Basin, central India. The first record of the widely distributed Turonian ammonoid genera Spathites Kummel and Decker and Collignoniceras Breistrof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The three-tiered Bagh Group is a mixed siliciclastic-carbonate succession comprising Nimar, Nodular Limestone and Bryozoan Limestone formations from the bottom to the top (Gangopadhyay & Maiti, 2012;Figs 2 and 3a), the age of which was originally assigned as Turonian-Coniacian on the basis of the ammonoid Placenticeratids (Chiplonkar & Ghare, 1976). Recent biostratigraphic investigation constrains Cenomanian, Turonian and Coniacian ages for the Nimar, Nodular Limestone and Bryozoan Limestone formations respectively (Kumar et al 2018).…”
Section: Geological Backgroundmentioning
confidence: 99%
“…The three-tiered Bagh Group is a mixed siliciclastic-carbonate succession comprising Nimar, Nodular Limestone and Bryozoan Limestone formations from the bottom to the top (Gangopadhyay & Maiti, 2012;Figs 2 and 3a), the age of which was originally assigned as Turonian-Coniacian on the basis of the ammonoid Placenticeratids (Chiplonkar & Ghare, 1976). Recent biostratigraphic investigation constrains Cenomanian, Turonian and Coniacian ages for the Nimar, Nodular Limestone and Bryozoan Limestone formations respectively (Kumar et al 2018).…”
Section: Geological Backgroundmentioning
confidence: 99%
“…In the western Narmada Basin of Gujarat, only the monospecific nektobenthic ammonite Placenticeras mintoi was reported in the Nimar Sandstone (Gangopadhyay and Bardhan, 2007;Jaitley and Ajane, 2013). However, by Turonian age, the sea-level transgression reached middle neritic depths in the eastern Narmada Basin of Madhya Pradesh supporting diverse ammonites in the Nodular Limestones (Gangopadhyay and Bardhan, 2007;Kumar et al, 2018).…”
Section: Late Cenomanian-early Turonian Oae2mentioning
confidence: 99%
“…The eastern Bagh Group has been extensively studied based on ammonoids, ostracods, echinoids, bryozoan, marine algae and planktic foraminifera with ages attributed to the Turonian-Coniacian (Jain 1975;Chiplonkar, 1982;Nayak, 1987;. A recent study of ammonites and inoceramids in the Nodular Limestone revealed early, middle and late Turonian deposition (Kumar et al, 2018). These deposits mark the eastward-reach of a sea-level transgression during the Turonian (Tandon, 2000;Tripathi, 2006;Bansal et al, 2020;Kumari et al, 2020) and unconformably overlie the predominantly continental Nimar Sandstone.…”
Section: Introductionmentioning
confidence: 99%
“…The Lower Cretaceous-Middle Cenomanian Malha Formation is overlain by the latest Middle and Early Late Cenomanian Galala Formation, which represents transgression in the basin concomitant with the Cenomanian eustatic sea-level rise . Abundant Thalassinoides burrows and ammonites of Cenomanian-Early Turonian are recorded from the upper part of the Galala Formation and the Nodular Limestone of the Bagh Group succession Kumar, Pathak, Pandey, Jaitly, & Gautam, 2018). The cross-bedded sandstones intercalated with shales or siltstones of shallow marine facies, oysters, and shallow carbonates at the base marks the onset of Cenomanian transgression, derived from the siliciclastics of the preexisting rocks in the Eastern Desert (Ismail et al, 2009) and in the Narmada Basin.…”
Section: Eastern Desert (Egypt)mentioning
confidence: 99%